2021
DOI: 10.1111/zsc.12516
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae)

Abstract: Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 50 publications
10
28
0
Order By: Relevance
“…1CZ to 83.6% in Stenochironomus sp. 3CZ (Table 2), showing a stronger A+T bias than other chironomid species [30][31][32][33]. Among the mitogenomes of Stenochironomus, the 3rd codon of PCGs and the control region exhibit the highest A+T content while the 1st and 2nd codons of PCGs have the lowest A+T content (Table 2).…”
Section: General Features Of Stenochironomus Mitogenomesmentioning
confidence: 99%
See 2 more Smart Citations
“…1CZ to 83.6% in Stenochironomus sp. 3CZ (Table 2), showing a stronger A+T bias than other chironomid species [30][31][32][33]. Among the mitogenomes of Stenochironomus, the 3rd codon of PCGs and the control region exhibit the highest A+T content while the 1st and 2nd codons of PCGs have the lowest A+T content (Table 2).…”
Section: General Features Of Stenochironomus Mitogenomesmentioning
confidence: 99%
“…2CZ failed to complete sequencing due to the complicated structure and high AT content. The entire length of mitogenomes of the Stenochironomus species is larger than other published chironomid species, mainly due to the large number of intergenic spacers [30][31][32][33]. Each mitogenome of Stenochironomus contains 37 typical genes (13 PCGs, two rRNAs, and 22 tRNAs) and one control region.…”
Section: General Features Of Stenochironomus Mitogenomesmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the Ka/Ks value between Diamesinae and other subfamilies of Chironomidae. Previous studies reported the Ka/Ks values of mitochondrial PCGs of Orthocladiinae and Stenochironomus (Lin et al, 2022;Zheng et al, 2022), and the Ka/Ks values of each PCG in these chironomids are higher than that in Diamesinae (Table S3), indicating that the mitochondrial genomes of Diamesinae are under stronger purifying selection than other nonbiting midge species (Hurst, 2002). Mitochondrial genome played a central role in animal energy production, and stronger purification selection could enhance their conserved role in energy production (Hassanin et al, 2009;Yuan et al, 2020).…”
Section: Evolutionary Ratementioning
confidence: 90%
“…Insect mitogenome is a 15 to 18 kb duplex circular DNA, generally encompassing 37 genes (13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA genes (rRNAs)), a control region (CR, or A + T rich region) and several shorter non-coding regions (NCRs) [ 18 ]. At present, the mitogenomic data have been extensively used in comparative genomics, phylogenetic and evolutionary analyses of different insect groups, including Diptera [ 19 , 20 , 21 , 22 , 23 ]. Acalyptratae is one of the most diverse lineages of Diptera comprising many species with economic and scientific importance [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%